Finding family : the duckling raised by loons - Salas, Laura Purdie (Millbrook Press, an imprint of Lerner Publishing Group, Inc., 2023)
"Discover the true story of an unlikely family -- an orphaned mallard duckling raised by a pair of loons. Lyrical verse and evocative illustrations combine in this heartwarming tale of animal cooperation"--